Frontotemporal Dementia: A Clinical Review - Dacka, Michał; Porzak, Mikołaj; Bochyński, Karol; Białogłowski, Konrad; Dąbrowska, Paulina; Żuber, Michał; Ciuba, Katarzyna; Molenda, Katarzyna; Borodziuk, Filip; Borodziuk, Barbara (Journal of Education, Health and Sport, 2024)
Frontotemporal dementia is a disease in which atrophic changes occur in the frontal lobes and frontal temporal lobes of the brain. Frontotemporal dementias are a clinically, neuroanatomically and pathologically diverse group of diseases that collectively constitute an important cause of young-onset dementia. The most common form of frontotemporal dementia is the so-called behavioral variant of frontotemporal dementia. Underlying these pathological changes is the degeneration of nerve cells (i.e. neurons), which occurs through the accumulation of abnormal proteins inside them. Therefore, the review of current studies in the subject of Frontotemporal dementia was conducted in order to access possible risk factors and new ways of management and treatment of this complex disease.